Consumer-Run Mental Health Framework for Recovery - Brown, Louis D.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
Consumer-Run Mental Health Framework for Recovery Louis D. Brown Conceived of as an empowering alternative to inpatient treatment and traditional community programs, mental health consumer-run organizations--CROs--offer consumers a hands-on stake in their own recovery. A growing evidence base suggests that CROs are a particularly effective form of self-help, with randomized trials demonstrating CRO participants experience improvements in personal empowerment, social integration, and well-being. Consumer-Run Mental Health explains their methods and analyzes their efficacy.  A robust theoretical framework synthesizes diverse perspectives to illuminate behavioral processes that contribute to recovery and the dynamics of CROs in creating environments that promote recovery. Data from the author's studies of CRO participation highlight consumer perceptions of the benefits of their involvement. An in-depth ethnographic study examines participant’s lives inside and outside the organization. And in a set of remarkable narratives, consumers describe dealing with both mental illness and the tasks of running a non-profit organization, for a fuller understanding of the impact of CRO participation on their lives.  By emphasizing consumer roles within the organization, the book breaks down the mental health CRO experience into these vital topics: ·                    Person-environment interaction within CROs. ·                    Developing empowering and socially supportive roles ·                    Resource exchange, skill development, and identity transformation ·                    Life history narratives: the lived experience of CRO participation. ·                    How organizations influence role development. ·                    The impact of role development on recovery. ·                    Implications for practice. Opening up about rarely-addressed concepts of self-help, Consumer-Run Mental Health is a unique reference for researchers who study peer-run organizations as well as practitioners in community mental health settings who are involved in collaborating with or  supporting CROs.
Chapter 1 – Introduction -- Chapter 2 - Using existing theory to build a conceptual framework of consumer-run organizations -- Chapter 3 - Refining the preliminary framework to create the role framework -- Chapter 4 - Constructing journalistic life history narratives to explore the role of framework -- Chapter 5 – Life history narratives from the P.S. Club -- Chapter 6 - Using narratives to understand how people benefit from CROs -- Chapter 7 – How Organizations Influence Role Development -- Chapter 8 – Role development and recovery -- Chapter 9 - Conclusion.
Keywords: Community psychology; Environmental psychology; Social work; Sociology; Community and Environmental Psychology; Social Work; Sociology, general